Role of Hypoxia in the Interferon Response - Arnaiz, Esther; Harris, Adrian L. (Frontiers in Immunology, 2022)
In solid tumors, as the tumor grows and the disease progresses, hypoxic regions are often generated, but in contrast to most normal cells which cannot survive under these conditions, tumour cells adapt to hypoxia by HIF-driven mechanisms. Hypoxia can further promote cancer development by generating an immunosuppressive environment within the tumour mass, which allows tumour cells to escape the immune system recognition. This is achieved by recruiting immunosuppressive cells and by upregulating molecules which block immune cell activation. Hypoxia can also confer resistance to antitumor therapies by inducing the expression of membrane proteins that increase drug efflux or by inhibiting the apoptosis of treated cells. In addition, tumor cells require an active interferon (IFN) signalling pathway for the success of many anticancer therapies, such as radiotherapy or chemotherapy. Therefore, hypoxic effects on this pathway needs to be addressed for a successful treatment.